Steady State Simulation and Analysis of Crude Distillation Unit at Baiji Refinery - Mohammed, Ayoob I.; Abdulla, Thaer A.; Hussein, Atta O. (Journal of Petroleum Research and Studies, 2024)
Abstract In this research work, the main distillation column of Salahadin 1 refinery in Baiji Refineries is simulated and analyzed using Aspen HYSYS. Kirkuk, Basrah and Ajeel crudes are mixed together (with unknown mixing ratio) to create the feed stream of this unit. The determination of the blending ratio of these streams beside performance analysis of the system using actual plant data to increase the operating capacity are the main objectives of this research work. So, this work is very helpful to the refinery because it can be applicable to manage these blending ratios to obtain desired product quality. Also, this work enables the CDU unit at the refinery to work at full capacity. The validation results show that the system is perfectly simulated with Aspen HYSYS and the mixing ratio of (Ajeel, Basrah, and Kirkuk) crudes are (0.102,0.5, and 0.398) respectively; Furthermore, this study suggested that, it is important to replace the transfer line pipe diameter between the furnace and the distillation column according to the design specifications which enables the operators to rise the feed volumetric flowrate into full capacity.